Amir's Anxiety and Motive in Khaled Hosseini's The Kite Runner - Ajeng Pancar Tamara; Muhammad Rifqi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
This paper discusses Amir’s anxiety and motive in Khaled Hosseini’s “The Kite Runner